2022
DOI: 10.1097/scs.0000000000008664
|View full text |Cite
|
Sign up to set email alerts
|

Design and Use of a Pair of Computer-Designed Surgical Templates in Reduction of a Comminuted Zygomatic Arch Fracture

Abstract: Background: Isolated depressed zygomatic arch fractures are often treated with closed reduction. Reduction is usually performed through the Gillies approach or Keen approach. comminuted zygomatic arch fractures generally require open reduction and fixation to achieve good results. This article describes how to use a pair of surgical templates to assist in the fixation of comminuted zygomatic arch fractures with absorbable plates. Methods: A pair of computer-designed surgical templates were applied to restore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…This usually happens due to severe trauma, such as a car accident or falling from a high place. Comminuted fractures can affect any bone in the body, but they are more common in long bones such as the femur, tibia, fibula, humerus, radius, and ulna [24]. One of the bones that can be affected by comminuted fractures is the zygomatic arch, which forms part of the cheekbone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This usually happens due to severe trauma, such as a car accident or falling from a high place. Comminuted fractures can affect any bone in the body, but they are more common in long bones such as the femur, tibia, fibula, humerus, radius, and ulna [24]. One of the bones that can be affected by comminuted fractures is the zygomatic arch, which forms part of the cheekbone.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that most patients who suffer from comminuted fractures in this bone suffer from noticeable asymmetry, and about 70% of them have significant asymmetry [25]. This causes the patient's dissatisfaction with the results of the treatment provided [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Gillies temporal approach has been widely used to reduce zygoma fractures 6–9 . Traditionally, it is the preferred method to reduce the isolated zygomatic arch fracture.…”
mentioning
confidence: 99%